HUBUNGAN KINERJA OTAK DENGAN SPIRITUALITAS DIUKUR MENGGUNAKAN INDONESIA SPIRITUAL HEALTH ASSESSMENT PADA GURU SMA DI TIDORE - Rachmatika, Ditha; Wongkar, Djon (e-Biomedik, 2014)
Abstract: The human brain is the center of the structure which has a volume around 1.350cc and consists of 100 million nerve cells or neuron. The human brain is responsible for the whole body and way of thinking. Brain also influential on human spirituality. Spirituality has 4 thing that can be observed is a ritual, spiritual experience, the meaning of life and positive emotions. Neuroscience is the science which studies human self as a pocess that takes at the level of neural cells to the human nexus with God.  Indonesian Spiritual Health Assessment is a checks are made based on the theoretical concept of the spiritual which consists of 3 components, namely spiritual health item, brain system assessment  and neurofeedback. Objective: Determine the relationship of spirituality human brain performance with high school teacher in the town of tidore. Methods: Type of observational study with cross-sectional research design. Study sample is a high school teacher in the town of Tidore totaling 65 people.  Data collected by distributing questionnaires to the respondents in the form of Indonesia Spiritual Health Assessment (ISHA). Result and Conclusion: Based on research that has been conducted on 65 subjects were obtained results that there is a relationship between the performance of human brain with spirituality. The result can be concluded that there is a relationship between the performance of the human brain with spirituality. The result can be concluded: (1) Cortex prefrontal have no association with a spiritual experience and the meaning of  life, but there is relationship with positive emotions and rituals; (2) system limbic have no association with spiritual experiences, positive emotion, the meaning of life and rituals; (3) ganglia basalis have no association with spiritual experiences, positive emotions and the meaning of life, but there is relationship with rituals; (4) gyrus cingulatus have no association with spiritual experiences, positive emotion and meaning of life, but there is relationship with rituals; (5) temporal lobe have relationship with spiritual experience, but no association with positive emotions, the meaning of life and rituals. Keywords: Brain performance, Spirituality.     Abstrak: Latar Belakang:Otak manusia adalah struktur pusat pengaturan yang memiliki volume sekitar 1.350cc dan terdiri atas 100 juta sel saraf atau neuron. Otak manusia bertanggung jawab terhadap pengaturan seluruh tubuh dan cara berpikir. Otak juga sangat berpengaruh terhadap spiritualitas manusia.Spiritualitas memiliki 4 hal yang dapat diamati yaitu ritual, pengalaman spiritual, makna hidup, dan emosi positif. Neurosains adalah ilmu yang mengkaji diri manusia sebagai proses yang berlangsung pada tingkat sel saraf hingga proses perhubungan manusia dengan Tuhan. Indonesia Spiritual Health Assessment adalah pemeriksaan yang dibuat berdasarkan konsep teoritis spiritualitas, yang terdiri dari tiga komponen yaitu Spiritual Health Item, Brain System Assessment, dan Neurofeedback. Tujuan: Mengetahui hubungan kinerja otak dengan spiritualitas manusia pada guru SMA di Kota Tidore. Metode: Jenispenelitian ini yaitu penelitian observasional dengan desain penelitian crosssectional.Sampel penelitian yaitu guru SMA di Kota Tidore Kepulauan yang berjumlah 65 orang. Data diambil dengan cara membagikan kuesioner yang berupa Indonesia Spiritual Health Assessment (ISHA) kepada responden. Hasil dan simpulan: Berdasarkan penelitian yang telah dilakukan pada 65 subjek penelitian diperoleh hasil yaitu ada hubungan antara kinerja otak dengan spiritualitas manusia. Dari hasil dapat disimpulkan bahwa: (1) Korteks prefrontal tidak ada hubungan dengan pengalaman spiritual dan makna hidup, tetapi ada hubungan dengan emosi positif dan ritual; (2) Sistem limbic tidak ada hubungan dengan pengalaman spiritual, emosi positif makna hidup dan ritual; (3) Ganglia basalis tidak ada hubungan dengan pengalaman spiritual, emosi positif dan makna hidup, tetapi ada hubungan dengan ritual; (4) Girus singulatus tidak ada hubungan dengan pengalaman spiritual, emosi positif dan makna hidup, tetapi ada hubungan dengan ritual; (5) Lobus temporal ada hubungan dengan pengalaman spiritual, tetapi tidak ada hubungan dengan emosi positif, makna hidup dan ritual. Kata Kunci: Kinerja Otak, Spiritualitas.